2020
DOI: 10.1007/s10151-020-02268-9
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility of intraoperative ultrasound of the small bowel during Crohn’s disease surgery

Abstract: Background Intraoperative assessment of the extent and location of Crohn's disease is not standardised and relies on a mixture of surgeons' experience, tactile feedback and macroscopic appearance. To overcome this variability, we developed a protocol for full intraoperative ultrasound scan of the small bowel and we here report the results of "Assessing the Feasibility and Safety of Using Intraoperative Ultrasound in Ileocolic Crohn's Disease-The IUSS CROHN Study". Methods This is a prospective single centre ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Intraoperative assessment needed to appreciate the extent and location of Crohn's disease has not been standardized and currently involves a mixture of surgeons' experience, tactile feedback, and macroscopic appearance. In a study titled "Assessing the Feasibility and Safety of Using Intraoperative Ultrasound in Ileocolic Crohn's Disease-The IUSS CROHN Study," Celentano and team [10] devised a strategy for a thorough intraoperative ultrasound scan of the small bowel to overcome this variability. This feasibility study mentioned above demonstrated the safety of intraoperative ultrasound and allowed the development of a standardized protocol for the intraoperative ultrasound.…”
Section: Several Applications Of Intraoperative Ultrasound In General Surgerymentioning
confidence: 99%
“…Intraoperative assessment needed to appreciate the extent and location of Crohn's disease has not been standardized and currently involves a mixture of surgeons' experience, tactile feedback, and macroscopic appearance. In a study titled "Assessing the Feasibility and Safety of Using Intraoperative Ultrasound in Ileocolic Crohn's Disease-The IUSS CROHN Study," Celentano and team [10] devised a strategy for a thorough intraoperative ultrasound scan of the small bowel to overcome this variability. This feasibility study mentioned above demonstrated the safety of intraoperative ultrasound and allowed the development of a standardized protocol for the intraoperative ultrasound.…”
Section: Several Applications Of Intraoperative Ultrasound In General Surgerymentioning
confidence: 99%
“…Intraoperative ultrasonography has been shown to minimise intraoperative assessment variability; when used, technical details and findings should be added to the report. 88,89 A phlegmon can contain different bowel loops and structures. The description of the perioperative findings should explain the surgical strategy.…”
Section: Surgical Indication and Strategymentioning
confidence: 99%